Evaluating Physicians’ Satisfaction with Using eHealth System for Managing Patients in Primary and Secondary Care - Denkovski, Viktor; Gavrilov, Goce; Stojmenovska, Irena; Radevski, Vladimir (EAI Endorsed Transactions on Pervasive Health and Technology, 2025)
INTRODUCTION: eHealth systems are raising both patient satisfaction and medical care. The proper workflow regulations and data exchange between primary and secondary healthcare are crucial.OBJECTIVES: Investigation of the major determinants influencing the physicians’ satisfaction while using an eHealth information system.METHODS: A survey of primary and secondary healthcare medical professionals was conducted in R.N. Macedonia. The categorical variables from the data analysis were presented and a logistic regression was carried out.RESULTS: The multiple logistic regression model was statistically significant for sufficient evidence to reject the null hypothesis in which the overall satisfaction rating of the eHealth system usage for managing patients and other healthcare services will not be affected by the other variables in favour of the alternative Ha.CONCLUSION: Various factors between primary and secondary healthcare professionals regarding system’s usage satisfaction are presented and studied. Various issues were revealed between both parties that should serve the policymakers and medical authorities for further improvements.
Keywords: eHealth system; physician satisfaction; patient management; eHealth services